Tortuosity of Terminal Arterioles in The Basal Ganglia Is Increased in Status Lacunaris. - Poni, Esteban S; Liwnicz, Boleslaw H; Ying-Ying, Yue; North, Mary (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The goal of this study was to evaluate the participation of small (diameter between 26 Âµm and 90 Âµm) and terminal (diameter between 10 Âµm and 25 Âµm) arterioles in the status lacunaris of the basal ganglia and to classify tortuous vascular profiles based on morphometry. Paraffin sections, 40 Âµm thick, of the basal ganglia from autopsied patients over the age of 45, were stained with PAS. A three-dimensional microscope, R400 (edge) was used to evaluate the structure of the blood vessels. Six patterns of the tortuous profiles were identified: simple kink, loop, knot, tangle, coil, and wave, as well as their combinations. Tortuous arterioles in the basal ganglia were present both in control group and status lacunaris cases. However, statistical Student”™s t-test analysis revealed a significant increment in the number of microfields containing tortuous terminal arterioles in the status lacunaris group (mean 7.50Ó4.62) versus the control group (mean 2.92Ó1.38) (p= 0.001). A risk for status lacunaris was associated with the increased frequency of tortuous terminal arterioles (Odd ratio=1.94, 95%-Confidence Interval=1.17-3.22) (p= 0.008) but not small arterioles (Odd ratio=1.64, 95%-Confidence Interval=0.62-4.38) (p= 0.39). Our findings suggest than an increased number of tortuous terminal arterioles is associated with status lacunaris. Six characteristic patterns of the tortuous profiles as well as their combinations were identified